IMPROVING THE QUALITY OF PATENT REGISTRATION SERVICES: AN APPLICANT SATISFACTION PERSPECTIVE AT THE DIRECTORATE GENERAL OF INTELLECTUAL PROPERTY - Sukma Ayudya Pramesti; Rezi Erdiansyah (CV. Radja Publika, 2023)
Introduction/Main Objective: Good governance will create good implementation of public service functions as well. On the other hand, bad governance means that public service functions will not be carried out well. Background of the Problem: researched the influence of the quality of patent registration application services on patent applicant satisfaction with DJKI based on reability, responsive, assurance, emphaty dan tangible. Research gaps/Novelty: This research examines the influence of the quality of patent registration application services on satisfaction of patent applicants at DJKI based on reability, responsive, assurance, emphaty dan tangible. Research Methods: This type of research is quantitative research with a cross sectional approach. This research uses the SPSS application. Finding/Result: There is a positive and insignificant influence between the quality of patent registration application services on patent applicant satisfaction with DJKI based on a reliability p-value > 0.05. There is a positive and significant influence between the quality of patent registration application services on patent applicant satisfaction with DJKI based on responsive, assurance, emphaty dan tangible. Conclusions and implications: This research shows that there are 4 indicators of service quality that influence patent applicant satisfaction with DJKI, so this can be of concern to DJKI to increase patent applicant satisfaction with DJKI.